Rheological Features of Aqueous Polymer Solutions Tailored by Hydrodynamic Cavitation - Santiago Nicolás Fleite; María del Pilar Balbi; María Alejandra Ayude; Miryan Cassanello (Fluids, 2025)
Hydrodynamic cavitation (HC) has emerged as a versatile method for modifying the rheological properties of polymer solutions, offering advantages such as scalability and operational simplicity. This work investigates the effect of HC on aqueous polyacrylamide (PAM) solutions, focusing on viscosity and viscoelasticity changes as a function of the number of passes through a vortex-type HC device and the presence of dissolved salts (CaCl2 or KCl). Viscosity measurements were modeled using the power law equation, while oscillatory tests were used to determine storage and loss moduli. The results show that HC substantially reduced viscosity and elastic behavior, with the degree of modification strongly influenced by the number of passes. A critical molecular size limit was suggested, below which further degradation becomes limited. Salt addition enhanced depolymerization, likely due to charge screening, hydrodynamic radius reduction, and the increased solubility and mobility of polymer chains within cavitation bubbles. HC eliminated elasticity in all cases, yielding solutions with near-Newtonian behavior. The transformation is attributed to molecular weight reduction and changes in molecular size distribution. These findings support the use of HC as a practical approach to tailor the flow properties of PAM solutions, while highlighting intrinsic limitations imposed by cavitation dynamics and polymer chain dimensions.